A Comparative Study Of Human Factors Influencing Health And Safety In Construction - Alrayes, Moutaz (Digital Repository of Theses - SSBM Geneva, 2025)
Health and safety (H&S) performance in the construction industry remains a concern globally, given the continuous high rates of accidents across both developed and developing countries. This dissertation investigates the factors influencing H&S performance, with particular emphasis on human factors compared to non-human elements, in a comparative study of the United Kingdom and Saudi Arabia. While many studies have examined health and safety, this research takes a comprehensive approach by categorising both human and non-human factors to identify those most critical to improving safety outcomes. This study adopted a mixed-methods approach to examine the role of human factors in shaping H&S outcomes. It started by developing a comprehensive definition of human factors—encompassing organisational systems, job design, and individual characteristics that influence behaviour at work. The study expanded existing definitions by showing that human factors extend beyond only individual behaviours. A structured questionnaire was completed by 164 construction professionals from the UK and Saudi Arabia. Their responses were statistically analysed to test four research hypotheses (RH1–RH4), comparing the influence of human factors against non-human elements such as economic, environmental, technological, and regulatory conditions. The quantitative phase was informed by an earlier qualitative stage. The findings confirm that human factors are the dominant drivers of H&S outcomes in both countries. Organisational dimension, job design, and individual capabilities each showed statistically significant influence, while non-human factors had minimal impact. Regulatory influences played a notable secondary role. Despite different regulatory frameworks, the rankings of human factor dimensions were consistent between the UK and Saudi Arabia. These results carry substantial implications. For practitioners, they emphasise the need to design jobs that match workers’ abilities, foster safety culture, and invest in worker development and supervision. Theoretically, the study extends understanding of human factors in construction, beyond individual behaviour to systemic influences. Ultimately, improving construction health and safety relies less on external systems and more on how people—organisations, teams, and individuals—interact with them. A human-centred approach, backed by regulation, offers the best path to safer construction environments. Keywords: Human factors, health and safety, construction industry, UK, Saudi Arabia, organisational dimension, job dimension, individual dimension, comparative study.